Safety and feasibility of synchronous unilateral nephrectomy and contralateral heminephrectomy for extremely severe autosomal dominant polycystic kidney disease: Techniques and outcome - Jang Hee Han; Seung-hwan Jeong; Hyeong Dong Yuk; Ja Hyeon Ku; Cheol Kwak; Hyeon Hoe Kim; Curie Ahn; Chang Wook Jeong (Investigative and Clinical Urology, 2022)
Purpose: To demonstrate the safety and feasibility of synchronous unilateral nephrectomy and contralateral heminephrectomy in extremely severe autosomal dominant polycystic kidney disease (ADPKD), which corresponds to the Mayo imaging classification classes 1D and 1E. Materials and Methods: We retrospectively reviewed patients who underwent unilateral nephrectomy and contralateral heminephrectomy at the Seoul National University Hospital (Seoul, Korea) between May 1, 2016 and August 1, 2021. The preoperative kidney volume was calculated using the ellipsoid equation (length×width×thickness×π/6). The Mayo imaging classification was determined by height-adjusted total kidney volume and age. Using a midline vertical incision, heminephrectomy was performed first by horizontal transection, followed by contralateral nephrectomy. Hilar vessel clamping or resection-bed suturing was not required. Results: In all, nine patients with ADPKD of the highest severity (Mayo class 1D/1E) underwent unilateral heminephrectomy and contralateral nephrectomy for the most common cause of severe abdominal discomfort and malnutrition. All nine patients had end-stage renal disease with hypertension and anemia. The median preoperative total kidney volume was 10,905.8 mL (interquartile range [IQR], 8,170.4–16,227.6 mL). The median operation time was 140 minutes (IQR, 125–185 min) and the median estimated blood loss was 250 mL (IQR, 200–425 mL). Eight of the nine patients were discharged without ICU care or any complications. Delayed pseudoaneurysm occurred in one case and was successfully managed by embolization. All patients were symptom-free for a median follow-up period of 2 years. Conclusions: Synchronous unilateral nephrectomy and contralateral heminephrectomy are safe and feasible treatment options for severe bilateral ADPKD.